2018
DOI: 10.1016/j.bpg.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of disease progression and incidence of complications in primary biliary cholangitis (PBC)

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…Cholestasis contributes to chronic granulomatous inflammation, which eventually leads to fibrosis and the subsequent development of cirrhosis and portal hypertension, along with its associated complications, including a predisposition to hepatocellular carcinoma (HCC). 43 With increasing awareness and understanding of the natural history of the disease, as well as earlier diagnosis and prompt treatment initiation, the progression to fibrosis and cirrhosis among PBC patients is becoming increasingly rarer, as demonstrated by the decrease in the indications of liver transplantation for PBC patients. 19,41,44 The introduction and use of UDCA for treating PBC has impacted the natural history of the disease.…”
Section: Natural Historymentioning
confidence: 99%
See 3 more Smart Citations
“…Cholestasis contributes to chronic granulomatous inflammation, which eventually leads to fibrosis and the subsequent development of cirrhosis and portal hypertension, along with its associated complications, including a predisposition to hepatocellular carcinoma (HCC). 43 With increasing awareness and understanding of the natural history of the disease, as well as earlier diagnosis and prompt treatment initiation, the progression to fibrosis and cirrhosis among PBC patients is becoming increasingly rarer, as demonstrated by the decrease in the indications of liver transplantation for PBC patients. 19,41,44 The introduction and use of UDCA for treating PBC has impacted the natural history of the disease.…”
Section: Natural Historymentioning
confidence: 99%
“…Patients with PBC are at an increased risk of developing HCC, though at a lower rate compared to those with other chronic liver diseases. 37,43 In a multicenter study involving over 4,500 patients over a 40-year period, Trivedi et al 57 showed that the incidence of HCC among PBC patients was 3.4 cases per 1,000 person-years. In particular, PBC patients with advanced age at diagnosis, advanced disease, male sex, and suboptimal response to UDCA are at higher risk for development of HCC.…”
Section: Pbc Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…PBC is characterised by T-lymphocyte-mediated destruction of the intrahepatic small bile ducts [ 6 ], cholestatic liver biochemistries, and the presence of antimitochondrial antibodies (AMAs) [ 7 ]. These highly disease-specific autoantibodies are directed against the E2 subunit of the pyruvate dehydrogenase complex and are present in 90–95% of PBC patients and less than 1% of healthy controls [ 8 , 9 ]. In PSC, circulating autoantibodies are not as frequent, but rather auto-inflammation is a more typical characteristic of the condition [ 10 ].…”
Section: Introductionmentioning
confidence: 99%